Optical cavities defined by SU-8 photoresist on photonic crystal waveguides - Lennon, S (2019)
A novel photonic crystal (PhC) cavity design is presented, for which the location of the cavity mode is determined by laser patterning of SU-8 – a commercially-available negative photoresist – on top of a conventionally-fabricated PhC waveguide. This method aims towards the goal of achieving deterministic coupling between a self-assembled InGaAs/GaAs quantum dot (QD) and a PhC cavity mode using in situ all-optical techniques. The experimental and theoretical work presented in this thesis focus on developing the technique to a stage at which it is ready for this intended application. The devices are designed to operate at a wavelength λ0 ~ 1.3 μm to be suitable for integration with telecommunications systems using commercially available optical fibres. Finite-difference time-domain (FDTD) simulations are performed to investigate key attributes of the SU-8 PhC cavities, which are believed to operate via a mode gap confinement mechanism, due to an alteration of the modes supported by the PhC waveguide beneath the SU-8 structure. Real devices are fabricated with high yields (generally exceeding 80%) and characterised predominantly using micro-photoluminescence (μPL) mapping techniques. The viability of the design is first demonstrated experimentally for cavities defined by exposing a disk of SU-8 on the waveguide, which yields fundamental cavity modes with a quality factor (Q) in the range 2300-7400 and a predicted mode volume V0 ~ 1.44 (λ0/n)3. The Q of the cavity mode is found to be critically depend upon the thickness of the SU-8: in general, a thickness of ~ 100 nm or less is preferable for optimal Q factors. An improved cavity design is devised which defines the cavity by a strip of SU-8 written perpendicular to the PhC waveguide. Higher Q factors up to 8700 are measured from fabricated devices and analysis suggests that cavity parameters are achieved which would be suitable for observing the strong coupling regime with a QD. The increase in Q factor is attributed primarily to the less stringent alignment requirements of the SU-8 strip cavity design. An investigation is also conducted into the effects of altering the width of the SU-8 strip, which allows the Q to be increased beyond 104 and also enables some control over λ0. However, it is expected that these results are ultimately limited by e-beam fabrication imperfections of the PhC waveguides. Finally, coupled cavities (known as photonic molecules) formed from two SU-8 strips written on the same waveguide are investigated through FDTD simulations and experiments. It is shown that the coupling strength between the two cavities can be tuned by controlling the separation between them. The coupled supermodes of the system are characterised and the coupling strength is estimated from measurements of the coupling-induced mode splitting and delocalization of the modes. Confocal μPL measurements are used to explicitly show optical coupling between two cavities.